2011
DOI: 10.1523/jneurosci.1513-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Associative Plasticity Induction in a Corticocortical Pathway of the Human Brain

Abstract: Coincident pairing of presynaptic and postsynaptic activity selectively strengthens synaptic connections, a key mechanism underlying cortical plasticity. Using paired associative transcranial magnetic stimulation (TMS), we demonstrate selective potentiation of physiological connectivity between two human brain regions, ventral premotor cortex (PMv) and primary motor cortex (M1) after repeated paired-pulse TMS of PMv and M1. The effect was anatomically specific: paired stimulation of the presupplementary motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
194
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(217 citation statements)
references
References 41 publications
20
194
3
Order By: Relevance
“…They then sought to induce plastic change in this connection by repetitively delivering 90 pairs of pulses (one pair every 10 s) with the same interstimulus interval (ISI) and the same coil positions. Buch et al (2011) found that stimulating PMv and M1 with an ISI of 8 ms significantly potentiated the inhibitory effect in the PMv-M1 paired-pulse paradigm, as the test-MEP size was reduced significantly. The effects of the PAS on functional connectivity were present for up to 1 h after intervention and reverted back to baseline at 3 h.…”
Section: Review Of Buch Et Al 2011mentioning
confidence: 86%
See 4 more Smart Citations
“…They then sought to induce plastic change in this connection by repetitively delivering 90 pairs of pulses (one pair every 10 s) with the same interstimulus interval (ISI) and the same coil positions. Buch et al (2011) found that stimulating PMv and M1 with an ISI of 8 ms significantly potentiated the inhibitory effect in the PMv-M1 paired-pulse paradigm, as the test-MEP size was reduced significantly. The effects of the PAS on functional connectivity were present for up to 1 h after intervention and reverted back to baseline at 3 h.…”
Section: Review Of Buch Et Al 2011mentioning
confidence: 86%
“…Buch et al (2011) asked whether paired associative stimulation (PAS) of interconnected areas of the cortex via noninvasive transcranial magnetic stimulation (TMS) might selectively induce Hebbian-like plasticity in a specific anatomical pathway in humans.…”
Section: Review Of Buch Et Al 2011mentioning
confidence: 99%
See 3 more Smart Citations